1996
DOI: 10.1021/jp9605257
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study on Phase Transition in Adsorbed Film of Fluoroalkanol at the Hexane/Water Interface. 1. Pressure Effect on the Adsorption of 1,1,2,2-Tetrahydroheptadecafluorodecanol

Abstract: The interfacial tension γ of hexane solution of 1,1,2,2-tetrahydroheptadecafluorodecanol (FC 10 OH) against water was measured as a function of pressure p and molality m 1 at 298.15 K. The break points were observed on the γ vs p and γ vs m 1 curves. The interfacial density Γ 1 H increases and the volume change associated with the adsorption ∆ν decreases with increasing m 1 , and they change discontinuously at concentrations of the break points. By drawing the interfacial pressure π vs area A curve, it is conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(99 citation statements)
references
References 24 publications
5
91
1
2
Order By: Relevance
“…where α is a factor defined by (17) α = m 1 m a N 2 + m 1 and approaches zero for large aggregates or/and high aggregate concentration. Furthermore y a is the average thermodynamic quantity of aggregate formation over all kinds of aggregates defined by…”
Section: Thermodynamics Of Aggregate Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…where α is a factor defined by (17) α = m 1 m a N 2 + m 1 and approaches zero for large aggregates or/and high aggregate concentration. Furthermore y a is the average thermodynamic quantity of aggregate formation over all kinds of aggregates defined by…”
Section: Thermodynamics Of Aggregate Formationmentioning
confidence: 99%
“…Also, in our previous paper [11], the enthalpy of mixing of oleyl alcohol and oils was measured by a high-accuracy isothermal calorimeter and the aggregation behavior of the alcohol molecules has been elucidated. On the other hand, it has been also reported that long-chain alcohols are adsorbed strongly from their oil solutions at the oil/water interfaces [3,[12][13][14] and their adsorbed films often exhibit a phase transition among gaseous, expanded, and condensed states, depending on the nature of alcohols and oils [15][16][17][18][19][20][21]. Usually, however, the aggregate formation in solution and the adsorption at the interfaces from the solution has been dealt with separately and their relation has been scarcely discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Let us call this choice of dividing surfaces the H convention. Then the interfacial tension is given as a function of the independent variable in the H convention by [19] where the quantities with the superscript H are, respectively, defined from Eqs. [12] to [14] as…”
Section: Thermodynamic Equations As a Function Of Temperature Pressumentioning
confidence: 99%
“…Denoting the solvent components air, water, and oil by 1, 2, and 3, respectively, the starting equation in the H convention Eq. [19] is simplified to…”
Section: A/w System With the Plane A/w Interface And Three Componentsmentioning
confidence: 99%
“…The phase transition of adsorbed films at air/water and oil/water interfaces has been extensively studied by many authors [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It is known that the van der Waals interaction between hydrophobic chains of amphiphiles plays an important role in it; for example, the condensed (twodimensional solid) adsorbed films of alkanols are observed even for shorter fluorocarbon chain (carbon number 10 is sufficient), although only for longer hydrocarbon chain (carbon number 18 is necessary), at the hexane/water interface under atmospheric pressure and ambient temperature [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%